Green synthesis of TIO2 NPS using ximenia caffra leaf extract and their application in poultry feeds as an antibacterial agent. - Mutoriti, Talent Tawanda (Midlands State University, 2017)
Phytosynthesis of TiO2 NPs from Ximenia Caffra leaf extract and their application in poultry feeds as an antibacterial agent was done. Reaction time and pH effect for the synthesis of TiO2 NPs were optimized using a single factor method. A Central Composite Design (CCD) was used to determine the effect of linear factors (titanium tetrachloride concentration, temperature and leaf extract volume) and their interactions on the synthesis of TiO2 NPs. A total of twenty experiments formulated from the central composite design were carried out, measuring absorbance as the response. Optimum conditions for the synthesis were 5 hrs, pH 7, 9 mM TiCl4, 11 ml extract and 33 ℃. UV-Vis and FT-IR techniques were used to characterize the synthesised nanoparticles. FT-IR spectra of synthesized TiO2 NPs exhibited prominent peaks at 3440 cm-1 phenol (O-H stretch), 3109.06 cm-1 carboxylic acids (O–H stretch), 2108.62 cm-1 alkynes and 1075.04 cm-1 (C–O) (stretch alcohols, carboxylic acids, esters). An absorption peak at 400 nm confirming the presence of TiO2 NPs was observed in the UV-visible spectrophotometric graph. Photocatalytic effect of the phytosynthesized TiO2 NPs and feed paste were tested by disc diffusion and colony forming unit methods against pathogenic E.coli. The minimum zone of inhibition were observed at concentration of 5 mg/ml (TiO2 NPs) and 11 mg/ml (TiO2 NPs Feed paste). Green synthesized TiO2 NPs indicates a promising approach that can satisfy their use as an antibacterial agent in poultry feeds.